Identification of biomarkers associated with CD8+ T cells in rheumatoid arthritis and their pan-cancer analysis - Zhao, Zhenyu; Ren, Jie; Xie, Siping; Zou, Longchun; Zhao, Qianyue; Zeng, Shan; Zha, Dingsheng (Frontiers in Immunology, 2022)
Introduction Rheumatoid arthritis (RA), a prevailing chronic progressive autoimmune disease, seriously affects the patient's quality of life. However, there is still a lack of precise treatment and management methods in clinical practice. Previous studies showed that CD8+ T cells take a lead in the progression of RA. Methods Genes closely related to CD8+T cells in RA were identified through multiple RA datasets, CIBERSORT, and WGCNA algorithms. Further machine learning analysis were performed to identify CD8+T cell-related genes most closely related to RA. In addition, the relationship between these three key genes and 33 cancer species was also explored in this study. Results In this study, 10 genes were identified to be closely related to CD8+T cells in RA. Machine learning analysis identified 3 CD8+T cell-related genes most closely related to RA: CD8A, GZMA, and PRF1. Discussion Our research aims to provide new ideas for the clinical treatment of RA.